The Effect of Taxpayer Perception and Trust in the Government on Taxpayer Compliance with the Voluntary Disclosure Program - Prihastuti, Asepma Hygi; Agusra, Dodi; Sofyan, Deviana; Sukri, Saipul Al (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to examine the effect of Taxpayer Perception and Trust in the Government on Taxpayer Compliance in the Voluntary Disclosure Program.The population in this study were all taxpayers registered at KPP Senapelan Pekanbaru. The sample used in this study were taxpayers who assisted in reporting the Annual Tax Return (SPT) in March 2022 at the Tax Center of the Persada Bunda School of Economics (STIE) which is the work area of ​​KPP Senapelan Pekanbaru, with a total of 95 respondents. The sampling technique used was non-probability sampling with an incidental sampling approach. This study uses primary data obtained through the distribution of questionnaires to individual taxpayers. The results this research state that Taxpayer Perception variable affect Taxpayer Compliance, variable Trust in Government affect Taxpayer Compliance, as well as Taxpayer Perception variable and Trust in the Government simultaneously affect Taxpayer Compliance with the Voluntary Disclosure Program. The independent variables, the perception of taxpayers and trust in the government are able to explain the dependent variable, namely taxpayer compliance by 31.3%, while the remaining 68.7% is explained by other variables not included in this research model.